Termination of Pregnancy by Rape Victim: the Dilemma in Malaysian Criminal Law - Rajamanickam, Ramalinggam; Kok Ann, Teh; Noor Azira Tengku Zainudin, Tengku; Azam Mohd Shariff, Ahmad (International Journal of Engineering and Technology, 2018)
Abortion is a complex issue as people have different views and reasons to terminate a pregnancy. The act of abortion does not only involves adults but also young girls. Generally, abortion is an offence punishable under the Penal Code of Malaysia. However, the issue of abortion becomes crucial when the abortion involves the victim of rape. The contending issue is to what extent does the Malaysian Penal Code legally allow the victim of rape to undergo an abortion. The provision that allows abortion is ambiguous in this context. Therefore, this article intends to analyse the legal position relating to abortion by rape victims in the Malaysian Penal Code. This article also serves to compare the position of abortion by victim of rape in India and Singapore. The article finds that the exception to the general principle on abortion in the Malaysian Penal Code is inadequate in protecting rape victims as compared to India and Singapore. Hence, it is urged that Malaysia should revise the law on abortion relating to victim of rape. However, some challenges have been identified before the country can amend the law.Â Â